Managing leadership towards 21 st. century - Seminar on Managing leadership towards 21st Century (1994 : Kuala Lumpur); International Islamic University Malaysia Student Affairs Division Leadership Training Department; International Islamic University Student Representetive Council Training and Research Secretariat (Kuala Lumpur : International Islamic University, 1994)
28